Relationship Between Patient Perceptions Of The Quality Of Inpatient Registration Services And Satisfaction Of Inpatients - Raisha Octavariny; Marice Simarmata (JURNAL KEBIDANAN KESTRA (JKK), 2022)
The hospital, as a referral level health service institution has the task of providing complete individual health services which include promotive, preventive, curative, and rehabilitative. Hospitals must meet the completeness of professional human resources, superior facilities where all of these indicators can affect service delivery to provide satisfaction to patients. This study aims to determine the relationship between patient perceptions of the quality of inpatient registration services and satisfaction of inpatients at GrandMed Hospital inpatient room, using an analytical survey research type. The sample of this study were 30 patients in the Ns 3D room using a questionnaire instrument. The sampling technique used is total sampling using the chi square test with a 95% confidence level = (0.05). The results showed that there was a relationship between inpatients’ perceptions of the quality of inpatient registration services based on responsiveness (P= 0.049 < (0.05) and empathy (P= 0.000 < (0.05) with inpatient satisfaction at Ns 3D GrandMed Hospital Lubuk Pakam. There is no relationship between inpatients’ perceptions about the quality of inpatient registration services based on tangible (P= 0.414 > (0.05), reliability (P= 0.283 > (0.005) and assurance (P= 0.783 > (0.05) with satisfaction of inpatients at Ns 3D Hospital GrandMed Lubuk Pakam. The results of this study are expected to be taken into consideration to improve the quality of services in the inpatient registration room at GrandMed Hospital.